2009
DOI: 10.1016/j.mce.2009.04.004
|View full text |Cite
|
Sign up to set email alerts
|

A paradigm of integrative physiology, the crosstalk between bone and energy metabolisms

Abstract: Thanks to integrative physiology, new relationships between organs and homeostatic functions have emerged. This approach to physiology based on a whole organism approach has allowed the bone field to make fundamental progress. In the last decade, clinical observations and scientific evidences in vivo have uncovered that fat with leptin controls bone mass through brain including a hypothalamic relay and sympathetic nervous system. The finding that energy metabolism affects bone remodelling suggested that in an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
179
1
8

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 214 publications
(196 citation statements)
references
References 61 publications
7
179
1
8
Order By: Relevance
“…(reviewed in refs (24) and (25) ). Leptin interacts directly or indirectly with these systems, thereby accounting for some of the differential effects reported for leptin in different bone compartments.…”
Section: Discussionmentioning
confidence: 99%
“…(reviewed in refs (24) and (25) ). Leptin interacts directly or indirectly with these systems, thereby accounting for some of the differential effects reported for leptin in different bone compartments.…”
Section: Discussionmentioning
confidence: 99%
“…Leptin is a gut and adipose tissue-derived hormone that regulates a range of biological functions and processes, including energy intake and expenditure, body fat, neuroendocrine systems, autonomic function, and insulin and glucose balance (12). Leptin receptors, LepRb, are located on neurons throughout the central nervous system as well as on VAN and other peripheral tissue.…”
mentioning
confidence: 99%
“…The contribution of the central role of leptin on neuroendocrine signaling in the hypothalamic region and its ultimately negative effects on (trabecular) bone formation, resorption, and bone mass by activating the sympathetic nerve signaling pathway has been amply demonstrated by a series of studies in at least 10 transgenic mouse models (mostly females) and has been confirmed by several intervention studies in other mouse models by the Karsenty group. (3,4) Several other groups, however, found leptin to have a positive effect on (mostly male) bone. Indeed, several studies did not confirm the increased bone mass in ob/ob mice (8,27) and found that, in contrast to the Karsenty data, peripheral leptin administration increased femoral length and bone mass in ob/ob mice.…”
mentioning
confidence: 97%
“…(1) Leptin then crosses the blood-brain barrier to activate its receptor in the hypothalamic regions, thereby starting a complex feedback on energy intake and expenditure but also regulating other systems such as sexual maturation and reproduction (2) and bone homeostasis. (3) Indeed, a series of elegant studies of the Karsenty group clearly demonstrated that central activation of leptin signaling activates the sympathetic postganglionic neuronal system that ultimately decreases bone formation and increases bone resorption. (3,4) Leptin receptors are also found outside the hypothalamus in insulin-producing b cells, bone marrow stromal cells, osteoblasts and chondrocytes, and kidney cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation